Mosaicism for duplication 12q (12q13–>q24.2) in a dysmorphic male infant. Issue 1 (January 1993) - Dixon, J W; Costa, T; Teshima, I E
Abstract : We report the clinical findings in a boy with mosaicism for a duplication of chromosome 12q13.1–>q24.2. His clinical characteristics are very similar to previously reported mosaic duplications of the distal long arm of 12, as well as several cases with non-mosaic duplications. It is proposed that this represents a clinically distinguishable syndrome for 12q duplication, in mosaic or non-mosaic form.